First record of black-chested fruiteater Pipreola lubomirskii (Aves, Cotingidae) in the western slopes of the Andes - Salinas, Letty (2003)
The black-chested fruiteater, Pipreola lubomirskii, is a cotinga reported as rare and of local distribution in the Northern Andes. Before the present report it only had been registered for the eastern slope of Peru and Ecuador, and in the southern Andes of Colombia. The present report extends its distribution to the montane forests of the Pacific slopes of Peruvian Andes, having been found in the cloud forests of the Zaña valley, in the department of Cajamarca (6º50’-6º52’ latitude S, 79º10’-79º07’ longitude W).